KONTROVERSI TENTANG OTENTISITAS HADITS DAN UPAYA ULAMA UNTUK MEMBELA OTENTISITASNYA - Herfin Fahri (Al Hikmah: Jurnal Studi Keislaman, 2014)
The Muslim scholars (ulama) have agreed on the highest position of the Qur'an for all Muslims. While, the position of the Prophet is in the second after the Qur'an. His position does not come from a community reception of the Prophet's presence as individual who has the power, but his position is clearly expressed through the God revelation. Allah has described the position of Prophet Muhammad in the structure as (a) the explainer of the Qur'an (b) the legislator, (c) the model for Muslim Society (d) the figure that must be followed by by society. Al-Hadith encompasses the human interaction that includes faith, moral, social and legal. The scholars of Hadith in the classical and contemporary era said that a hadith can be called sahih (authentic) if it is in line with four conditions: (1) It was narrated with sanad (chains of narration) which is muttashil (continuous) from the last narrator recording the hadith up to the Prophet as the source of hadith (2) the narrators were composed of people who have such properties as adl and dhabit. (3) the hadith does not contain the so-called syaz, (4) the hadith does not contain the so-called illat. If the four conditions were met, then it could be called authentic hadits.